Influence of Nesting Characteristics on Health of Wild Bee Communities - Harmon-Threatt, Alexandra (Annual review of entomology, 2020)
Nest site availability and quality are important for maintaining robust populations and communities of wild bees. However, for most species, nesting traits and nest site conditions are poorly known, limiting both our understanding of basic ecology for bee species and conservation efforts. Additionally, many of the threats commonly associated with reducing bee populations have effects that can extend into nests but are largely unstudied. In general, threats such as habitat disturbances and climate change likely affect nest site availability and nest site conditions, which in turn affect nest initiation, growth, development, and overwintering success of bees. To facilitate a better understanding of how these and other threats may affect nesting bees, in this review, I quantify key nesting traits and environmental conditions and then consider how these traits may intersect with observed and anticipated changes in nesting conditions experienced by wild bees. These data suggest that the effects of common threats to bees through nesting may strongly influence their survival and persistence but are vastly understudied. Increasing research into nesting biology and incorporating nesting information into conservation efforts may help improve conservation of this declining but critical group.